2012
DOI: 10.3390/ijms131215496
|View full text |Cite
|
Sign up to set email alerts
|

Identification of kakusei, a Nuclear Non-Coding RNA, as an Immediate Early Gene from the Honeybee, and Its Application for Neuroethological Study

Abstract: The honeybee is a social insect that exhibits various social behaviors. To elucidate the neural basis of honeybee behavior, we detected neural activity in freely-moving honeybee workers using an immediate early gene (IEG) that is expressed in a neural activity-dependent manner. In European honeybees (Apis mellifera), we identified a novel nuclear non-coding RNA, termed kakusei, as the first insect IEG, and revealed the neural activity pattern in foragers. In addition, we isolated a homologue of kakusei, termed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…Prior to this work, only two lncRNAs had been described in honey bees [32], [33], [37], these being expressed in the brain of adult bees. Hence, with only four lncRNAs identified so far, the analysis of this class of transcripts has not even reached infancy in the honey bee, this standing in utter contrast with knowledge on honey bees microRNAs, and even more so with the human transcriptome where lncRNAs now comprise the largest fraction amongst noncoding RNAs [38].…”
Section: Discussionmentioning
confidence: 99%
“…Prior to this work, only two lncRNAs had been described in honey bees [32], [33], [37], these being expressed in the brain of adult bees. Hence, with only four lncRNAs identified so far, the analysis of this class of transcripts has not even reached infancy in the honey bee, this standing in utter contrast with knowledge on honey bees microRNAs, and even more so with the human transcriptome where lncRNAs now comprise the largest fraction amongst noncoding RNAs [38].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, in honey bees, only four lncRNAs have been identified so far in terms of their possible functions. These are two lncRNAs identified from studies on brain transcriptomes (Sawata et al 2002(Sawata et al , 2004Kiya et al 2012) and the two abovementioned lncRNA genes revealed from the ovarian transcriptomes (Humann and Hartfelder 2011), which were subsequently named long noncoding ovary 1 (lncov1 ) and long noncoding ovary 2 (lncov2 ). Both turned out to have an intronic location in the sense strand of protein-coding genes, one (lncov1 ) in a gene of unknown function, only defined by computational prediction, and the other (lncov2 ) in the honey The honey bee ovary bee homolog of fringe.…”
Section: Gene Expression Analyses Reveal Molecular Mechanisms Underlymentioning
confidence: 99%
“…Extensive studies carried out in this area have revealed that the products of IEGs play an essential role in diverse molecular events underlying learning and memory processes by modification of functional properties in the activated neural circuitry, such as transcriptional activation of secondary activity‐regulated genes (also known as delayed early genes), regulation of membrane receptor trafficking, and promotion of neuritegenesis (Loebrich & Nedivi, ; Leslie & Nedivi, ; West & Greenberg, ). By contrast, far fewer studies have been conducted in insects compared to vertebrates, and only three genes, kakusei , Early growth response protein ( Egr ) and Hormone receptor‐like in 38 ( Hr38 ), exhibiting clear neural activity‐dependent rapid expression have been reported (Kiya et al ., ; Fujita et al ., ; Ugajin et al ., ). Egr and Hr38 are proposed to be conserved IEGs in vertebrates and insects (Fujita et al ., ; Lutz & Robinson, ; Ugajin et al ., ), whereas homologues of kakusei are found only in bees (family Apidae).…”
Section: Introductionmentioning
confidence: 99%